Acoustic Echo Cancellation with Arbitrary Playback Sampling Rate - Stokes, Jay; Malvar, Henrique S. (Institute of Electrical and Electronics Engineers, Inc., 2004)
This paper introduces a new architecture for implementing subband acoustic echo cancellation (AEC) with arbitrary playback sampling rate. Typically, in AEC algorithms for audio or video conferencing, the sampling rates for the signals played through the speakers and captured from the microphones are identical. For speech recognition while playing CD-quality music and Internet gaming with voice chat, the playback sampling rate is usually higher than the capture rate. A direct solution is to apply a sampling rate converter to the playback signal before feeding it to the AEC, but that is complicated if many sampling frequencies must be supported. We propose a more efficient solution for subband AEC: we perform the sampling rate conversion as a frequency-domain interpolation that matches the transform lengths of the playback and capture signals. Results show that the new AEC architecture has a small computational cost and only a minimal reduction in echo attenuation.